Education and Training Empowerment for Posbindu Cadres to Prevent Non-Communicable Diseases in Sendangmulyo Village, Semarang City - Qomariah, Nurul; Widiyanto, SY. Didik; Wikandari, Ririh Jatmi; Kuncara, Rachmad Bayu (Jurnal Ilmiah Pengabdian Masyarakat Bidang Kesehatan (Abdigermas), 2024)
The purpose of this PPDM is to strengthen the cadre of Posbindu PTM officers in 3 RW of Sendangmulyo village in order to provide optimal health services and how to increase awareness of their own health and family, so as to reduce the number of NCD patients. The targets of PPDM are cadres of Posbindu PTM Officers in RW 15, 20 and 24 Sendangmulyo urban villages, Tembalang sub-district, Semarang City. The method used is education, training 15 cadres of Posbindu PTM officers, to be implemented during Posbindu PTM in their RW routinely in the form of health counseling) and providing services for checking blood pressure, weight, height, abdominal circumference, cholesterol, uric acid and blood sugar, as well as consulting services about complaints felt by residents, then conducted monitoring and evaluation by pengabdi related to improving the quality of health services carried out by cadres of Posbindu PTM officers after being trained. The results obtained are that residents feel more able to know their health conditions so that they can improve their health conditions on the basis of direction, advice from officers at table 5 and the quality of service is getting faster, dexterous, and looks skilled in the use of tools.